Hubungan Riwayat Hipertensi Dan Pola Makan Dengan Kejadian Preeklamsia Pada Ibu Hamil - Suryaningsih, Merlyna; Zainiyah, Zakkiyatus; Aini, Qurrotu; Ernawati, Ernawati (NHM PRESS, 2024)
Preeclampsia is one of the main contributors to morbidity and mortality in mothers and fetuses. From the preliminary study in October-December 2022, 141 pregnant women and 47 (31.31%) pregnant women with preeclampsia were obtained. The purpose of this study is to analyze the relationship between history of hypertension and diet with the incidence of preeclampsia in pregnant women. This study used a correlation analytical design with the Cross Sectional approach. The independent variable were history of hypertension and diet and dependent variable was incidence of preeclampsia. The population was 141 pregnant women with a large sample of 47 respondents using purposive sampling techniques. Data collection using questionnaires and observation sheets with relationship tests using Spearman Rank with a =0.05 The results of statistical tests on the history of hypertension with preeclampsia were obtained P = 0.000 <a = 0.05 with a correlation of 0.500 there was a relationship between the history of hypertension and the incidence of preeclampsia and obtained P = 0.001 < With a correlation of (–) 0.484 there was an relationship between diet and the incidence of preeclampsia It is recommended for pregnant women and mothers who are still planning to get pregnant to maintain their diet well, so as to avoid the occurrence of preeclampsia, while mothers who have a history of hypertension during pregnancy are expected to be aware of the appearance of symptoms of preeclampsia , nurses are expected to socialize the importance of maintaining a diet both before pregnancy and during pregnancy, especially pregnant women with preeclampsia.